2022
DOI: 10.32604/jrm.2022.016903
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin-Conjugated Polylactic Acid Nanobubbles Encapsulated Perfluoropentane as a Contrast Agent for Ultrasound/Magnetic Resonance Dual-Modality Imaging

Abstract: The development of contrast agents that can be activated by multiple modes is of great significance for tumor diagnosis. In this study, the lactoferrin (Lf)-conjugated polylactic acid (PLLA) nanobubbles (Lf-PLLA NBs) were used to encapsulate liquid perfluoropentane (PFP) with the double emulsion method, creating PFP loaded (PFP/ Lf-PLLA) NBs for the ultrasound/magnetic resonance dual-modality imaging of subcutaneous tumor. The particle diameter and stability of nanobubbles were investigated by photon correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Among the most commonly used polymers are PVA and PLA. Mostly polymer-based microbubbles respond at a high-frequency range upon ultrasound due to stiff shells [ 2 , 16 , 53 , 54 ]. Brismar et al synthesize incorporated salinized SPIONs and loaded them in 2% PVA solution and achieved a contrast effect in both ultrasound (5 MHz) and MRI (3 T) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most commonly used polymers are PVA and PLA. Mostly polymer-based microbubbles respond at a high-frequency range upon ultrasound due to stiff shells [ 2 , 16 , 53 , 54 ]. Brismar et al synthesize incorporated salinized SPIONs and loaded them in 2% PVA solution and achieved a contrast effect in both ultrasound (5 MHz) and MRI (3 T) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of dual-mode contrast studies are focused on high-frequency applications, while most abdominal and cardiac examination involves 3.5 MHz frequency ultrasound [ 15 , 16 , 60 , 61 ]. In this study, microbubbles demonstrated successful enhancement at a frequency of 3.5 MHz in a 0.3 T MRI system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation